Knowledge About the Common Risk Factors Among Patients Presenting with Acute Stroke - Saddam, Muhammad; Khan, Saeed Ahmed; Ahmed, Hussain; Ali, Abdul; Hussain, Saddam; Gul, Sur; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Stroke is a leading cause of death and disability. Many survivors lack awareness of key stroke risk factors. Objective: To identify awareness gaps and assess understanding of stroke risk factors among acute stroke patients. Methods: Simple random sampling was used to select 100 consecutive patients (≥18 years old) with clinically diagnosed acute ischemic or hemorrhagic stroke for this qualitative, descriptive study. A semi-structured questionnaire covering seven major risk factors (hypertension, diabetes mellitus, smoking, high cholesterol, obesity, sedentary lifestyle, and family history), sources of prior information, and perceived cause of stroke was used to interview mentally competent patients who were able to participate. Responses were calculated as frequencies and percentages, and demographic and clinical data were documented. Results: With 56% of the cohort being male, the mean age distribution was 10% (18–30 years), 28% (31–50 years), 42% (51–70 years), and 20% (>70 years). The highest levels of awareness were for diabetes (66%) and hypertension (72%), while smoking (58%), high cholesterol (49%), obesity (41%), sedentary lifestyle (38%), and family history (45%) were less common. 84% of respondents said they had at least one modifiable risk factor, 36% said they had non-modifiable risks, 29% said they had both, and 8% said they had no discernible hazards. Of those who had no prior information, 25% cited media (24%), family/friends (28%), and healthcare professionals (33%). 42% of respondents named hypertension as the primary cause of their stroke, followed by stress (18%), diabetes (14%), smoking (9%), and uncertainty (17%). Conclusion: Knowledge gaps persist on key stroke risk factors. Structured, multimodal educational efforts are crucial for effective secondary prevention.